Distribution of Urocortins and Corticotropin-Releasing Factor Receptors in the Cardiovascular System - Kazuhiro Takahashi (International Journal of Endocrinology)
Urocortins are human homologues of urotensin I, a fish corticotropin-releasing-factor- (CRF-) like peptide secreted from the urophysis. There are three urocortins: urocortin 1, urocortin 2, and urocortin 3 in mammals. We have shown that urocortin 1 and urocortin 3 are endogenously synthesized in the myocardial cells of human heart and may act on CRF type 2 receptor (CRFR2) expressed in the heart. Expression levels of urocortin 1 in the heart and plasma urocortin 1 levels are elevated in patients with heart failure. Recent studies have shown that urocortins have various biological actions in the cardiovascular system, such as a vasodilator action, a positive inotropic action, a cardioprotective action against ischemia/reperfusion injury, and suppressive actions against the renin angiotensin system and the sympathetic nervous system. Urocortins and CRFR2 may therefore be a potential therapeutic target for cardiovascular diseases, such as congestive heart failure, hypertension, and myocardial infarction.